2004
DOI: 10.1002/bjs.4694
|View full text |Cite
|
Sign up to set email alerts
|

Continuous infusion ofN-acetylcysteine reduces liver warm ischaemia–reperfusion injury

Abstract: The main protective effect of NAC becomes apparent 5 h after hepatic ischaemic injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
48
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 38 publications
4
48
0
1
Order By: Relevance
“…8 Pharmacological and surgical interventions have been developed aiming at attenuating the problems inherent in I/R injury. [9][10][11] Ischemic preconditioning (IP)-a short period of ischemia followed by a period of reperfusion prior to the prolonged ischemia-seems to confer protection against the longer ischemic period and subsequent reperfusion insult. 12 Extensive experimental studies and a few clinical series have shown that IP is beneficial not only for the liver but for a variety of other tissues subjected to I/R.…”
Section: Introductionmentioning
confidence: 99%
“…8 Pharmacological and surgical interventions have been developed aiming at attenuating the problems inherent in I/R injury. [9][10][11] Ischemic preconditioning (IP)-a short period of ischemia followed by a period of reperfusion prior to the prolonged ischemia-seems to confer protection against the longer ischemic period and subsequent reperfusion insult. 12 Extensive experimental studies and a few clinical series have shown that IP is beneficial not only for the liver but for a variety of other tissues subjected to I/R.…”
Section: Introductionmentioning
confidence: 99%
“…Glutathione precursors such as N-acetylcysteine, bucillamine, and possibly S-adenosylmethionine could be more effective in situations associated with severe intracellular oxidative stress. Our experimental studies in animals with normal or steatotic livers, undergoing lobar warm liver I/R injury, 12,13 and in a small randomized clinical trial in patients undergoing liver resections, 14 showed beneficial effects of N-acetylcysteine administration. However, a pilot prospective randomized clinical trial on the administration of N-acetyl cysteine to donors, in human liver transplantation, also by our own group, showed no objective evidence of clinical benefit, perhaps highlighting the difficulty of tailoring a therapy without a readily-measurable end-point.…”
mentioning
confidence: 72%
“…The diversity of pharmacological applications of NAC is mainly due to the chemical properties of the cysteinyl thiol group of its molecule, since the ability of reduced thiol groups to scavenge ROS and reactive nitrogen species has been well established [11][12][13]. Consequently, NAC was widely used in clinical practice as an antioxidant and had been investigated whether it was beneficial for reducing liver ischemiareperfusion (IR) injury in animal models [11][12][13].…”
Section: Introductionmentioning
confidence: 98%